(untitled) (Economic and Political Thought, 2018)
In the changing environment, it is necessary to create conditions conducive to the creation of entities that base their competitive advantage on knowledge. Knowledge becomes a strategic factor for the development and growth of competitiveness. Knowledge-based economy, the new economy, the network economy in the knowledge society are new directions for the development of the modern world. The article presents the essence, basics and carriers of knowledge-based economy, and discusses selected definitions of knowledge-based economy. It indicates and discusses the characteristics of knowledge-based economy formulated by selected authors. It presents the entities that influence the creation of knowledge-based economy. It shows that knowledge is the basic resource in an organization. The author discusses the essence and the need for knowledge management, indicates the goals and aspects of knowledge management and presents selected factors influencing the functioning of the knowledge management system.